The Urgency of Islamic Ethnoscience-Based Science Learning in the 4.0 Era - Cahyadi, Ani; Fiteriani, Ida; Samson, Nur-Aida Tahirulla; Hapsari, Mega Tunjung (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Entering the Industrial Revolution 4.0 era, science learning in elementary schools faces the challenge of becoming more digital, contextual, and meaningful. However, conventional approaches that are still predominantly textual and abstract are considered less relevant to students' local culture and Islamic values. This study aims to analyze the urgency of an Islamic ethnoscience-based science learning approach as a solution to the gap between science material, culture, and spiritual values. This study employs a qualitative approach, with an exploratory case study conducted at an Islamic-based Elementary School in South Kalimantan from January to May 2025. Research participants included five science teachers, 3 Banjar cultural figures, 2 Islamic education experts, and students in grades IV–VI. Data collection techniques included in-depth interviews, participant observation, and documentation studies of teachers, cultural figures, and Islamic education experts. The results show that conventional science learning has not explicitly linked the material to the local culture (the Banjar tribe) and Islamic values, resulting in low student engagement and a lack of meaning. The Islamic ethnoscience approach is considered capable of integrating cultural, religious, and technological values through digital learning media such as interactive e-books and contextual content based on the Quran. This research makes a significant contribution to developing a science education paradigm that is more grounded in spirituality and adaptable to the challenges of modern technology-based education.